An Investigation of the Genetics of Sporulation in Bacillus subtilis - Roy, Robert G. (My University, 1967)
The investigation was carried out in order to eliminate a hypothetical sporulation factor from wild-type strains of Bacillus subtilis using agents know to remove episomes. The subsequent investigations produced no mutants with properties predicted for strains missing the sporulation factor. When cells were exposed to UV light prior to treatment with acridine dyes there was, however, a significant increase in the production of normal sporulation mutants.
Title: An Investigation of the Genetics of Sporulation in Bacillus subtilis, Author: Robert G. Roy, Location: Thode